Queer Fragmentation and Trans Urban Aesthetics: from Cyberpunk to Cottagecore (Glocalism: Journal of Culture, Politics and Innovation, 2022)
Queerness and transidentity have had a durable relationship with cyberpunk aesthetics, reflected in both cultural works and academic reflections. There is an evident attraction in worlds where technological prowess allows one to evolve beyond one’s corporeal body, or to change it at will. The noir explorations of themes such as discrimination and sex work are also strong sources of resonance with common trans and queer experiences. Culturally, this aesthetic is indissociable from its urban component, with the serendipity, diversity, and density of the city often at the centre of the stories told. This reflects the observed tendency of queer people to congregate in urban centres, where minorities are present in sufficient numbers to create social communities with freer explorations around gender. This appeared to be one of the central aesthetic currents of the global trans community until the early twenty-first century. However, we now observe a change with the rise of more rural aspirations, exemplified by the recent popularity of the cottagecore aesthetic. There seems to be a growing desire to retreat from society at large and isolate in tight-knit homogeneous communities, replacing co-spatiality with online connectedness. This could be the result of multiple factors, among which two seem central: the assimilation of many queers linked to the dissolution of greater federated queer communities, and the increased prioritisation of online interactions. Drawing from human geography, literary analysis and a corpus from Tumblr (a microblogging network) this article thus seeks to explore how aspirational and representational depictions of queerness evolved in tandem with its physical and online practices, transforming the historically close relationship between queerness and urbanity.
Keywords: cyberpunk; cottagecore; metronormativity; spatialities; queer fragmentation